Pengaruh Gadget Terhadap Daya Tangkap Siswa SD - Shafira Andani (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Nowadays technology is developing increasingly rapidly, nowadays gadgets are not only used by adults, but also used by teenagers and children. Humans are very dependent on gadgets, the use of gadgets has become an important part of life. Gadgets can make it easier to access and reach anything. However, gadget addiction is very vulnerable to children. One of the initial factors causing this could be the child's parents, who are willing to give them a gadget just to make their child calm when they cry. This often happens in everyday life and this is the factor that makes children become dependent on gadgets. And another case that makes children dependent on gadgets is because of online games that children like, such as free fire, mobile legend and pubg games.